2018
DOI: 10.26758/8.1.7
|View full text |Cite
|
Sign up to set email alerts
|

Parental stress and bedtime routines in toddlerhood

Abstract: Objectives. Main purposes of our study were to explore: a) the relationship between paternal and maternal perceptions of their interactions with the child during bedtime routines; b) the possible relationship among context dimensions (social support, marital satisfaction, parenting stress and bedtime routines). We examined both parents' subjective experience toward children's bedtime routines and their personal relationship with going to sleep. Results. Correlations outcome evidenced positive relationships bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 15 publications
2
4
0
Order By: Relevance
“…However, we confirmed the fourth hypothesis (H4), highlighting paternal involvement in children's bedtime care as a protective factor for sleep quality [24,33]. Our data confirm the results of previous studies showing associations between higher levels of maternal stress and bedtime difficulties, less favorable child sleep profiles, and challenging bedtime routines [15,16]. Regarding parental involvement, several studies identified a relationship between paternal factors and children's sleep patterns [19].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…However, we confirmed the fourth hypothesis (H4), highlighting paternal involvement in children's bedtime care as a protective factor for sleep quality [24,33]. Our data confirm the results of previous studies showing associations between higher levels of maternal stress and bedtime difficulties, less favorable child sleep profiles, and challenging bedtime routines [15,16]. Regarding parental involvement, several studies identified a relationship between paternal factors and children's sleep patterns [19].…”
Section: Discussionsupporting
confidence: 89%
“…Hughes et al [15] observed that mothers of 9-month-old infants with less favorable sleep profiles reported depressive symptoms, poorer self-reported health, and significant levels of parenting stress. De Stasio and colleagues [16] found that mothers and fathers who reported significant levels of parental distress tended to describe their toddlers' bedtime routines as particularly challenging.…”
Section: Introductionmentioning
confidence: 99%
“…From our results maternal stress represents a risk factor for the increasing night awakenings, instead paternal involvement in children's bedtime care appear to act as protective factors for sleep quality (Dahl & El-Sheikh, 2007). Our data confirm previous studies showing associations between higher levels of maternal stress and bedtime difficulties, less favorable child sleep profiles, and challenging bedtime routines (Hughes et al, 2015;De Stasio et al, 2018). Regarding parental involvement, several studies identified a relationship between paternal factors and children's sleep patterns (Bernier et al, 2016).…”
Section: Discussionsupporting
confidence: 88%
“…Higher levels of stress and depression are negatively associated with parental warmness and reciprocity [36], which are both crucial factors in caregiver-child interactions at bedtime and in general for good quality sleep in children. Only a few studies have also involved fathers by exploring the relationship between paternal parenting stress, children’s sleep problems and parent-child sleep interactions at bedtime [11, 29, 30]. The existing research suggests that fathers experience similar perinatal affective disorders to mothers, such as, for example, post-partum depression [31, 32].…”
Section: Discussionmentioning
confidence: 99%